2007
DOI: 10.1073/pnas.0700070104
|View full text |Cite
|
Sign up to set email alerts
|

Concerted ATP-induced allosteric transitions in GroEL facilitate release of protein substrate domains in an all-or-none manner

Abstract: The double-ring chaperonin GroEL mediates protein folding, in conjunction with its helper protein GroES, by undergoing ATPinduced conformational changes that are concerted within each heptameric ring. Here we have examined whether the concerted nature of these transitions is responsible for protein substrate release in an all-or-none manner. Two chimeric substrates were designed, each with two different reporter activities that were recovered after denaturation in GroES-dependent and independent fashions, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Detailed studies have revealed mechanistic and physiological characteristics of the isologous ring form of the GroEL/S machine (11,42,45,53,54). According to the current understanding, the following properties of GroEL are significant in controlling its activity: (i) oligomerization mediated by the equatorial domain, resulting in the formation of the folding chamber and the encapsulation of substrate polypeptides (48, 59); (ii) recognition of substrate polypeptides medi- (32,63,64); and (iv) ATP hydrolysis (19,55). Impairment of any of these properties significantly alters the functioning of GroEL (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies have revealed mechanistic and physiological characteristics of the isologous ring form of the GroEL/S machine (11,42,45,53,54). According to the current understanding, the following properties of GroEL are significant in controlling its activity: (i) oligomerization mediated by the equatorial domain, resulting in the formation of the folding chamber and the encapsulation of substrate polypeptides (48, 59); (ii) recognition of substrate polypeptides medi- (32,63,64); and (iv) ATP hydrolysis (19,55). Impairment of any of these properties significantly alters the functioning of GroEL (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that stable misfolded FTrho-like polypeptides, similar to the 82-kDa aconitase (14), need not fully enter the chamber and stay under a sealed GroES lid suggests that large polypeptides with several misfolded domains might be catalytically unfolded domain by domain, as shown to be the case with chimerical rhodanese fused to GFP or dihydrofolate reductase (31). CCT also was suggested to assist multidomain protein refolding in a domain-by-domain manner, thus mimicking optimal cotranslational folding (32).…”
Section: Discussionmentioning
confidence: 96%
“…To explore the full effect of GroEL dynamics, from now on, we use the coupled time-dependent equations [Eq. (12)]. In vitro experiments can be used to measure the time-dependent yield of the native state of SPs as a function of GroEL, GroES, and ATP concentrations.…”
Section: The Allosteric Kinetic Model Accounts For [El]-dependent Folmentioning
confidence: 99%
“…1 that it is important to account for the coupling between the complex allosteric transitions that the GroEL particle undergoes and the fate of the SP during the reaction cycle in order to describe the workings of the GroEL-GroES machine. 4,[12][13][14][15][16] Studies that artificially simplify the processes in the GroEL cycle ( Fig. 1), such as using SPs that do not require GroES or mutants from which GroES does not dissociate on biologically relevant timescales, while insightful, cannot accurately represent the mechanism of rescue of stringent SPs under nonpermissive conditions.…”
mentioning
confidence: 98%